The translation of Serge Poliakoff’s Enluminures by Jean Chuzeville - Gamalova, Natalia (Literatūra, 2025)
The book Enluminures is a facsimile of a ‘notebook’ illustrated with paintings of the abstract artist Serge Poliakoff. It was published by the Swiss publisher Erker-Verlag in 1972. The book contains twenty-seven photolithographs and handwritten ‘verses’ composed in Russian by Serge Poliakoff. The text was translated into French by Jean Chuzeville, and the painter hand-wrote the French version. The name of the translator is mentioned on the last page, wherever the book’s editorial information is made available, in German. Painting catalogues and collected articles about Serge Poliakoff regularly quote ‘verses’, in French, from this book – yet they hardly ever mention the name of the translator.There are at least four possible approaches of interest to analysing Poliakoff’s ‘notebook’: firstly, the circumstances surrounding the conception and publication of the book, secondly, questions about the dialogue between painting and text, and thirdly, the ‘verses’ of the painter, who turned to ‘poetry’ for the first time in his life. Finally, the translation of the artist’s ‘verses’ into French attracts scholarly attention. An analysis of the Russian original text and its French translation shows that the French version surpasses the Russian original in terms of syntax, richness of vocabulary, coherence, and probably the literary quality as well.
Keywords: Poliakoff (Serge); Chuzeville (Jean); book-object; translation; literality